Genotoxic and histopathological effects of the Ili River (Kazakhstan) water pollution on the grass carp Ctenopharyngodon idella. Issue 1 (31st December 2022) - Tlenshieva, Arshyn Muratkyzy; Witeska, Malgorzata; Shalakhmetova, Tamara Minazhevna
ABSTRACT: In the present study, genotoxic, histological and hematological effects of water pollution were evaluated in Ctenopharyngodon idella from the Ili river. Water and fish were sampled at three sites. The concentrations of the following heavy metals were measured in the water: Pb, Co, Mg, Cd, Cu, Zn, Fe. Water pollution with metals gradually increased from P1 to P3: in P1, Cu and Fe levels exceeded the maximum permissible concentrations for fish culture, in P2 – Pb, Cu, Zn, Fe, and in P3 – Pb, Cd, Cu, Zn, Fe. In fish from the Ili river, the highest frequency and severity of DNA damage and liver damage were noted in P3, the lowest in P1. Gill lesions were more pronounced and frequent in fish from P3 compared to grass carp from P2 and P1. Fish from P1 showed a higher frequency of neutrophils and a lower percentage of lymphocytes compared to the control. The results also revealed: genotoxicity measured by comet analysis and liver histology were the most sensitive and showed the magnitude of lesions directly related to the level of water contamination. Gill histology also clearly showed pathological changes caused by pollution, while differential leukocyte count was the least useful indicator, as it showed only minor differences between fish from unpolluted and polluted water.